1917 [videorecording (DVD)] - Mendes, Sam; Scott, Andrew, 1976 October 21-; Cumberbatch, Benedict, 1976-; Madden, Richard, 1986-; Strong, Mark, 1963- (Universal Pictures Home Entertainment, 2020)
At the height of the First World War, two young British soldiers, Schofield and Blake, are given a seemingly impossible mission. In a race against time, they must cross enemy territory and deliver a message that will stop a deadly attack on hundreds of soldiers.